Traceability Technology in Plastic Waste Management for Recycling Paper Industry: A Circular Economy Review - Rapati, Rr. Citra; Marimin, Marimin; Arkeman, Yandra; Nurhayati, Popong (Indonesian Journal of Sustainability Accounting and Management, 2025)
The global increase in plastic waste generation poses a significant challenge to environmental sustainability. Among major contributors is plastic waste from the recycling paper industry. The circular economy represents an emerging paradigm in the management of plastic waste in Indonesia. Despite growing interest in digital innovations, the integration of traceability technology such as blockchain and IoT remains underexplored. This study explores the role of smart technology in enhancing traceability of plastic waste management within the recycling paper industry in the context of the circular economy framework using the PRISMA protocol. Through a systematic literature review of 40 peer review from Scopus and ProQuest published between 2013 and 2024, the study highlights the current practices, drivers, and barriers in adopting smart technologies, while enabling alignment with sustainability reporting frameworks like the Global Reporting Initiative (GRI) and the Sustainability Accounting Standards Boards (SASB). This review contributes to the field of sustainability accounting by framing digital traceability of plastic waste not only as technical solution but also as a driver of ESG aligned innovation. The findings propose a future research agenda to explore innovative approaches and solutions for optimizing plastic waste traceability in line with sustainable practices and circular economy principles.